The Concept of Asbabun Nuzul in the Context of Warfare: A Tafsir Ahkam Study of QS. Al-Baqarah: 190-193 Based on Tafsir Al-Qurtubi - Munir, Muhammad Syamsul; Ramadhani, Regita Dyah; Masruhan, M; Kholid, Ibrahim Nasrullah (QiST: Journal of Quran and Tafseer Studies, 2025)
The Concept of Asbabun Nuzul in the Context of Warfare: A Tafsir Ahkam Study of QS. Al-Baqarah: 190–193 Based on Tafsir Al-Qurtubi, explores the concept of asbabun nuzul and legal rulings (ahkam) within the war-related verses of the Qur'an. Focusing on Al-Qurtubi's tafsir, the research analyzes the historical and socio-political contexts surrounding the revelation of QS. Al-Baqarah: 190–193. Utilizing a library-based method and historical-contextual approach, it investigates both the background of revelation and its legal implications. Al-Qurtubi's interpretation highlights key Islamic principles in warfare, such as justice, self-defense, and the prohibition of transgression, especially toward non-combatants. The findings affirm that these verses provide ethical guidance in protecting civilians and limiting harm. The study also discusses the contemporary relevance of these principles in the framework of international law, particularly concerning the right to self-defense and civilian protection. Ultimately, this research contributes to the ongoing discourse on Islamic jurisprudence and its application in modern global contexts, emphasizing the value of classical exegesis in shaping fair international policies.